Stray dog - Kurosawa, Akira 1910-.; Kikushima, Ryuzu 1914-.; Mifune, Toshiro 1920-.; Shimura, Takashi 1905-. ([Japan] Shintoho Production, 1949)
When detective Murakami loses his revolver, he descends into Tokyo's underworld to find the killer who has taken it. Set in Tokyo during the late 1940s, the film captures the chaos and humiliation that existed in Japan immediately after World War II.
VHS
Videocassette release of the 1949 motion picture.
In Japanese with English subtitles.
Geijutsusai Grand Prize winner in 1949.
Toshiro Mifune, Takashi Shimura.